Impact of London Toxicity Charge and Ultra Low Emission Zone on NO2. (December 2022) - Prieto-Rodriguez, Juan; Perez-Villadoniga, Maria J.; Salas, Rafael; Russo, Ana
Highlights: A diff-in-diff model estimates the effect of London traffic policies on NO2 levels. Toxicity Charge (TC) and Ultra Low Emission Zone (ULEZ) improve air quality. These two traffic policies reduce NO2 in the city centre and, also, in nearby areas. No border effects due to the TC or the ULEZ are observed. Ultra Low Emission Zone leads to larger cuts in NO2 levels than Toxicity Charge.